2003
DOI: 10.1177/082585970301900108
|View full text |Cite
|
Sign up to set email alerts
|

The Cultural Differences in Perceived Value of Disclosure and Cognition: Spain and Canada

Abstract: A previous multicentre international study on sedation at the end of life has detected major differences between Canadian and Spanish patients. This was particularly evident in the need to sedate Spanish patients for psychological/existential distress. This study was designed to explore the hypothesis that marked differences in the value patients and families attach to disclosure and cognition were a factor. The study population included patients referred to two palliative care consulting services based in acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…International comparisons described southern European countries as partial and non-disclosure countries [221], [222], [223] and Spanish awareness studies suggested that this trend persisted over time [194], [204], [218], [224], [225], [226], [227]. On the other hand, studies with healthy populations show that preferences are evolving towards open disclosure [201], [202], [203], [204], [207], [228].…”
Section: Resultsmentioning
confidence: 99%
“…International comparisons described southern European countries as partial and non-disclosure countries [221], [222], [223] and Spanish awareness studies suggested that this trend persisted over time [194], [204], [218], [224], [225], [226], [227]. On the other hand, studies with healthy populations show that preferences are evolving towards open disclosure [201], [202], [203], [204], [207], [228].…”
Section: Resultsmentioning
confidence: 99%
“…(2003) described how the relative and the patient did not openly discuss the fact that the patient was dying, as that could precipitate the patient's death. Fainsinger et al. (2003) reported that relatives and patients in Canada wanted full information, in contrast to relatives and patients in Spain.…”
Section: Resultsmentioning
confidence: 99%
“…6 When the outlook is poor, family members should be told. 7 When the outlook is poor, family members should be asked if the patient should be told 8 When discussing prognosis, I try to be as direct, clear and specific as possible 9 In my work setting, I am expected to discus matters first with the family and only later with the patient 10 Most family concerns about disclosure of information to the patient are exaggerated 11 It is best to give information to patients stepwise rather than 'all at once' 12 When discussing prognosis, I try to be as general as possible 13 I try to guide patients to the treatment that I feel is best for them 14…”
Section: Nevermentioning
confidence: 99%
“…Although patients vary in the degree to which they want to be medically informed and to thereby participate in the decision-making process, surveys of patient preferences indicate that the overwhelming majority of patients in Western countries [11][12][13][14][15][16][17][18][19], and substantial proportion of patients in non-Western countries [13,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38], want disclosure of information to participate in the decision-making process. Universally, recent survey data of patient preferences demonstrate substantial heterogeneity of preferences that are not individually predictable by geography, culture, age, race, sex or educational level [11][12][13][14][15][19][20][21][22][23][24][25][26][27][28][29][30]…”
mentioning
confidence: 99%